Kajian Dasar Mikrobiologi dan Protein Sambal Tempoyak : Inovasi Pengawetan Produk Lokal menuju Agroindustri Berkelanjutan - Arafah, Elmeizy; Sari, Selly Ratna (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2025)
Local products have distinctive and original flavors from various regions. Bengkulu City is known for producing durian, which is commonly processed into products such as lempok, dodol, pancakes, curry, and chili sauce. Sambal tempoyak, a popular dish, is often stored for extended periods. However, the storage process typically involves refrigeration, which requires special handling when serving. Removing the tempoyak from cold storage can lead to contamination and a reduction in nutritional content due to repeated heating. Therefore, it is important to explore the addition of certain ingredients and determine optimal storage durations to preserve sambal tempoyak. The purpose of this study is to analyze the microbiology and protein levels in sambal tempoyak during storage. The research method used is a completely randomized design (CRD) with treatments at 0 days (A0), 2 days (A1), 4 days (A2), and 6 days (A3).The results of the study showed that the total plate count after 6 days remained within the SNI standard, which is less than 1x104. The protein content was consistent, with an increase in protein levels observed on the third day from 1.52% to 1.64%.The study recommends that sambal tempoyak can be stored for more than 6 days at room temperature. The addition of specific ingredients can act as natural preservatives, supporting the preservation of local products and contributing to a sustainable agroindustry.